Pemberdayaan Komunitas Gay dan Waria Melalui Health Promotion Model dan Budidaya Tanaman Hidroponik: Empowering Gay and Transgender Communities Through Health Promotion Models and Hydroponic Plant Cultivation - Wulandari, Yuanita; Sa'diyah, Halimatus; Firman, Firman; Daesusi, Ruspeni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Currently, the number of global HIV cases has reached 37.7 million people, and around 680,000 to 1 million people die every year due to HIV/AIDS. Meanwhile, in Indonesia, currently, HIV cases continue to increase from year to year; new findings are estimated to reach 7,650 people, compared to 7,036 people in the previous year. The high number of HIV cases in Indonesia is caused by several methods of massive transmission that are less controlled, including through heterosexuals (51.5%). This study aims to empower gay and Transgender Communities Through Health Promotion Models and Hydroponic Plant Cultivation—methods for implementing activities, in the form of lectures, discussions, and practice. The training, which was held for 2 days, effectively increased participants' knowledge and changed attitudes. Evidenced by significant changes in knowledge levels, the results of the pretest knowledge were high at 26.5%, then after the post-test, knowledge increased to 91.2%. Meanwhile, the pretest results for respondents' good attitude were 15%, and after the post-test, good attitude increased significantly to 100%. Thus, it is hoped that with the knowledge and changes in attitudes of the participants, it can prevent and reduce the number of HIV cases in the gay and transgender community in the Pacar Kembang sub-district, Surabaya.